2023
DOI: 10.3390/su151914396
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Policies on the Sustainable Greenhouse Development in Biskra Region (Algeria)

Toufik Aidat,
Salah Eddine Benziouche,
Leonardo Cei
et al.

Abstract: Since its appearance in Algerian agriculture, the greenhouse production system has turned the agricultural sector upside down, bringing great advantages for production in terms of quality and quantity, creating a very important socio-economic dynamic, especially in the Saharan region. This paper makes a new contribution by providing information on the impact of agricultural policies on greenhouse development in Biskra (southeastern city in Algeria). This study aims to understand the type of farms/farmers most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The relationship between sustainable agricultural policies and various factors can be complex. For example, a study in Algeria found that farmers who used land acquisition and financing policies were less likely to specialize in greenhouse production, suggesting that these policies may not always lead to the desired outcomes [11]. Another study in China found that land transfer can significantly improve the level of agricultural green production, but it can also inhibit it, depending on various factors such as the family's long-term agricultural labor, social capital, migrant experience, non-agricultural income, and household clean energy use [12].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sustainable agricultural policies and various factors can be complex. For example, a study in Algeria found that farmers who used land acquisition and financing policies were less likely to specialize in greenhouse production, suggesting that these policies may not always lead to the desired outcomes [11]. Another study in China found that land transfer can significantly improve the level of agricultural green production, but it can also inhibit it, depending on various factors such as the family's long-term agricultural labor, social capital, migrant experience, non-agricultural income, and household clean energy use [12].…”
Section: Introductionmentioning
confidence: 99%